DETECÇÃO DE ANTICORPOS PARA LEPTOSPIRA SPP. EM ANIMAIS E FUNCIONÁRIOS DO ZOOLÓGICO MUNICIPAL DE UBERABA, MG - Esteves, F. M. [UNESP]; Guerra-Neto, G. [UNESP]; Girio, R. J. da S. [UNESP]; Silva-Vergara, M. l.; Carvalho, A. C. de F. B. [UNESP] (Instituto Biológico, 2022)
The objective of the present study was to detect antibodies against Leptospira spp. by the microscopical seroagglutination test in animals and employees of the municipal zoo of Uberaba, MG. Blood samples of 166 animals including mammals, reptiles, fish and poultry and of the 36 employees were collected. Of all studied animals, 17 (10.02%) were reactant to antibodies against Leptospira spp. The sorovars found in the different species were: Grippotyphosa in a Cerdocyon thous species; Canicola in a Chrysocyon brachiurus species; Andamana and Icterohaemorrhagiae in 2 species of Leopardus pardalis ; Canicola and Icterohaemorrhagiae in 2 species of Puma concolor; Icterohaemorrhagiae in two species of Tayassu tajacu; Andamana in 2 species of Geochelone spp.; Patoc in a Trachemys scripta specie; Canicola in six species of Oreochromis niloticus; Icterohaemorrhagiae in a Rattus rattus specie. The most frequent sorovars were Canicola 8 (47.05%); Icterohaemorrhagiae 5 (29.41%) and Andamana 2 (11.76%). The titer 1/100 was the strongest with 35.3% in all reactant agents. The poultry, the stray domestic cats and the employees of the zoo were negative for the analyzed sorovars. In all studied species, the mammals and the fish presented the most seroactivity. The importance of more studies in both wild and captive animals and the relevance to Leptospira epidemiology can be seen.

O presente estudo teve como objetivo detectar anticorpos contra Leptospira spp. pelo teste de soroaglutinação microscópica em animais e funcionários do Zoológico Municipal de Uberaba, MG. Foram colhidas amostras de sangue de 166 animais entre mamíferos, répteis, peixes e aves e dos 36 funcionários. Dos animais estudados, 17 (10,24%) foram reagentes para anticorpos contra Leptospira spp. Os sorovares encontrados nas diferentes espécies foram: Grippotyphosa em uma espécie Cerdocyon thous (Cachorro-do-mato); Canicola em uma espécie Chrysocyon brachiurus (Lobo-Guará); Andamana e Icterohaemorrhagiae em duas espécies Leopardus pardalis(Jaguatirica); Canicola e Icterohaemorrhagiae em duas espécies Puma concolor (Suçuarana); Icterohaemorrhagiae em duas espécies Tayassu tajacu (Cateto); Andamana em duas espécies Geochelone spp. (Jabuti); Patoc em uma espécie Trachemys scripta (Tigre d’água); Canicola em seis espécies Oreochromis niloticus (Tilápia); Icterohaemorrhagiae em uma espécie Rattus rattus (Rato de telhado). Os sorovares mais freqüentes foram Canicola 8 (47,05%); Icterohaemorrhagiae 5 (29,41%) e Andamana 2 (11,76%). O título 100 foi o mais prevalente com 35,3% entre as espécies reagentes. As aves os gatos domésticos errantes e os funcionários do zoológico foram negativos para os sorovares analisados. Dentre as espécies estudadas, os mamíferos e os peixes apresentaram maior sororeatividade. Destaca-se a importância de mais estudos em animais silvestres e em de cativeiro e sua relevância no contexto da epidemiologia da Leptospirose.
DETECTION OF ANTIBODIES AGAINST LEPTOSPIRA SPP. IN ANIMALS AND EMPLOYEES OF THE MUNICIPAL ZOO OF UBERABA, MG, BRAZIL
Keywords: Leptospirosis; sorovars; zoonosis; wild animals; zoo; Leptospira; sorovar; zoonose; animais silvestres; zoológico